Filtering for discrete-time nonhomogeneous Markov jump systems with uncertainties - Yin, Y.; Shi, P.; Liu, F.; Teo, Kok Lay (Elsevier Inc, 2014)
This paper studies the problem of robust H1 filtering for a class of uncertain discrete-time nonhomogeneous Markov jump systems. The time-varying jump transition probability matrix is described by a polytope. By Lyapunov function approach, mode-dependent and variation-dependent H1 filter is designed such that the resulting error dynamic system is stochastically stable and has a prescribed H1 performance index. A numerical example is given to illustrate the effectiveness of the developed techniques.